2021
DOI: 10.1016/j.proci.2020.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of soot formation from evaporating fuel films by laser-induced fluorescence and incandescence

Abstract: Late-evaporating liquid fuel wall films are considered a major source of soot in gasoline directinjection engines. In this study, a direct-injection model experiment was developed to visualize soot formation in the vicinity of evaporating fuel films. Isooctane is injected by a multi-hole injector into a wind tunnel with an optically accessible test section. Air flows continuously at low speed and ambient pressure through the test section. Some of the liquid fuel impinges on the quartz-glass windows and forms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The accurate measurements on soot volume fraction and ame temperature play a remarkable role in depth revealing the impact of CO 2 on soot formation. The laser spectrum detection has been employed in the combustion diagnosis, the high precision measurements of soot volume fraction can be achieved via the light extinction (LE) technology, [23][24][25] and laserinduced uorescence (LIF) technology. [23][24][25] The soot volume fraction in the C 2 H 4 counterow diffusion ame was calculated by Wang et al 26 employing the LE technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate measurements on soot volume fraction and ame temperature play a remarkable role in depth revealing the impact of CO 2 on soot formation. The laser spectrum detection has been employed in the combustion diagnosis, the high precision measurements of soot volume fraction can be achieved via the light extinction (LE) technology, [23][24][25] and laserinduced uorescence (LIF) technology. [23][24][25] The soot volume fraction in the C 2 H 4 counterow diffusion ame was calculated by Wang et al 26 employing the LE technology.…”
Section: Introductionmentioning
confidence: 99%
“…The laser spectrum detection has been employed in the combustion diagnosis, the high precision measurements of soot volume fraction can be achieved via the light extinction (LE) technology, [23][24][25] and laserinduced uorescence (LIF) technology. [23][24][25] The soot volume fraction in the C 2 H 4 counterow diffusion ame was calculated by Wang et al 26 employing the LE technology. The experimental studies proved that the decrease of soot volume fraction was 25.2% with 20% CO 2 -F. M. Sirignano et al 27 revealed that the decrease in soot volume fraction was 65% with the CO 2 -O using the LIF technology.…”
Section: Introductionmentioning
confidence: 99%
“…Kollpe, et al [6] had measured piston surface temperature in a GDI engine using a thinfilm thermocouple embedded piston. Furthermore, they investigated the influence of various parameters such as injection pressure and injection timing on detail temperature history of piston top.…”
Section: Introductionmentioning
confidence: 99%